Penerapan Prinsip Prinsip Good Corporate Governance Pada Rumah Sakit Airlangga Jombang - Anggraeni, Nikken Eva Ayu; Djasuli, Mohamad (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
In the current era of globalization, technological developments are increasingly advanced and have led to increasingly fierce competition in the business world. The impact of the existence of competition is pressing companies to maintain and improve their company's performance. This is because the company's performance is the basic thing that investors look at to assess a company so that they can make the right decision to invest their funds in the company. The purpose of this study was to determine the application of the principles of Good Corporate Governance at Airlangga Jombang Hospital. This study uses qualitative methods and data collection techniques using semi-structured interviews. The results of research at Airlangga Jombang Hospital in the implementation of the principles of Good Corporate Governance show that companies still have deficiencies in implementing Good Corporate Governance on the principles of transparency, responsibility and independence where they are not fully transparent regarding financial reports to directors, there are still employees who violate company regulations , salaries that do not match the District Minimum Wage, and employees work not in accordance with the job description,